2015
DOI: 10.1039/c4ra13118e
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic block copolymer terminated with pyrene group: from switchable CO2-temperature dual responses to tunable fluorescence

Abstract: Py-PCL-b-P(NIPAM-co-DMAEMA) micelles can present switchable CO2-temperature dual responses and tunable fluorescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
(40 reference statements)
2
20
0
Order By: Relevance
“…217 In the first step Py-PCL was synthesized by ring-opening polymerization (ROP), and then reacted with S-dodecyl-S 0 -(a,a 0 -dimethyl-a 00 -acetic acid)trithiocarbonate (DDMAT) to produce Py-PCL-DDMAT. 217 In the first step Py-PCL was synthesized by ring-opening polymerization (ROP), and then reacted with S-dodecyl-S 0 -(a,a 0 -dimethyl-a 00 -acetic acid)trithiocarbonate (DDMAT) to produce Py-PCL-DDMAT.…”
Section: Reversible Deactivation Radical Polymerization (Rdrp)mentioning
confidence: 99%
See 1 more Smart Citation
“…217 In the first step Py-PCL was synthesized by ring-opening polymerization (ROP), and then reacted with S-dodecyl-S 0 -(a,a 0 -dimethyl-a 00 -acetic acid)trithiocarbonate (DDMAT) to produce Py-PCL-DDMAT. 217 In the first step Py-PCL was synthesized by ring-opening polymerization (ROP), and then reacted with S-dodecyl-S 0 -(a,a 0 -dimethyl-a 00 -acetic acid)trithiocarbonate (DDMAT) to produce Py-PCL-DDMAT.…”
Section: Reversible Deactivation Radical Polymerization (Rdrp)mentioning
confidence: 99%
“…The schematic self-assembly process of Py-PCL-b-P(NIPAM-co-DMAEMA) and the CO 2 -temperature dual responses 217. Reprinted from ref.…”
mentioning
confidence: 99%
“…The conversion of living ROP products containing a terminated hydroxyl group into macro-RAFT agents is simply through esterification with carboxylic acid-containing RAFT agents that provided many examples of mechanistic transformation of ROP -Ŧ-RAFT. [152][153][154][155][156][157][158][159] Moreover, instead of esterification, the terminal hydroxyl groups of the living ROP products could easily convert to chloride or bromide compounds, and then reacted with the xanthogenate group to afford the macro-CTAs for further RAFT/MADIX polymerizations. [160][161][162][163][164][165][166][167] Dove and O'Reilly et al [168,169] reported a series of PLAb-PAA diblock copolymers with a range of hydrophobic or hydrophilic block lengths, which formed cylindrical micelles by crystallization-driven self-assembly (CDSA) approach.…”
Section: Rop -ŧ-Raftmentioning
confidence: 99%
“…The conversion of living ROP products containing a terminated hydroxyl group into macro‐RAFT agents is simply through esterification with carboxylic acid‐containing RAFT agents that provided many examples of mechanistic transformation of ROP ‐Ŧ‐ RAFT . Moreover, instead of esterification, the terminal hydroxyl groups of the living ROP products could easily convert to chloride or bromide compounds, and then reacted with the xanthogenate group to afford the macro‐CTAs for further RAFT/MADIX polymerizations …”
Section: Transformations From Ropmentioning
confidence: 99%
“…17 Subsequently, polymers containing CO 2 -responsive functional groups such as amine 18 and imidazole 19 have been prepared and their applications have been studied extensively in reversible protein absorption, 20 carbon nanotube dispersion, 21 drug release, 22 switchable emulsion 23 as well as tunable surfaces. 24 Among these applications, CO 2 -responsive morphology evolution of polymer assemblies represents an intriguing issue as it may serve as a model for studying drug release 25,26 as well as promoting the understanding of cellular shape transformation and stimuli-responsive nanoreactors. [27][28][29][30] Several CO 2 -responsive block copolymers have been elegantly exploited to prepare vesicles and nanotubes, which would reassemble into wormlike micelles and spherical micelles upon CO 2 triggering.…”
Section: Introductionmentioning
confidence: 99%